Preventing Extinction Language with Socio Cultural Activities: an Empirical Study on Duano Sea Tribe - Diana Rozelin; Mailinar Mailinar; Ulfatmi Azlan (Journal of Language and Literature, 2026)
Many languages worldwide are currently endangered. Many linguists argue that endangered languages can be preserved through revitalisation and language documentation. Others contend that languages used by minority communities will inevitably disappear and be replaced by those of majority communities. This article focuses on investigating and describing the condition of the Sea Tribe language through dialectological and sociocultural perspectives among the Duano Sea Tribe in Sabak and Tungkal. This research employs a qualitative approach, using interviews, recordings, and documentation for data collection. The findings indicate that not only language revitalisation and documentation, but also sociocultural activities, can reduce the risk of language endangerment. This article argues that sociocultural activities play a significant role in reducing the vulnerability of endangered languages. This is evident in the sociocultural domain of knowledge systems, where, although the Duano language is not used in schools in both areas, it continues to be used at home. Furthermore, systems of material culture and technology are more present in Sabak but are rare in Tungkal. This study makes an empirical contribution by demonstrating that the failure to revitalise a language through sociocultural activities may lead to language death.